2021
DOI: 10.1038/s41598-021-03007-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and soluble receptor for advanced glycation end-products play a role in the pathophysiology of delirium after cardiac surgery

Abstract: Coronary-artery bypass graft (CABG) surgery is known to improve cardiac function and decrease mortality, albeit, this method of treatment is also associated with a neuropsychiatric complications including postoperative delirium. The pathophysiology of delirium after cardiac surgery remains poorly understood. Thus, the purpose of this study was to investigate whether oxidative stress reflected by decreased preoperative and postoperative plasma antioxidant activity is independently associated with delirium after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…ROS produced excessively would mediate detrimental effects, which are known as oxidative stress ( Rosenfeldt et al, 2013 ). It has been demonstrated that perioperative oxidative stress is associated with the increased risk of postoperative delirium ( Karlidag et al, 2006 ; Lopez et al, 2017 , 2020 ; Kazmierski et al, 2021 ). Similarly, in the present study, we found that anesthesia/surgery induced ROS accumulation and delirium-like behavior, while the ROS scavenger NAC attenuated these changes.…”
Section: Discussionmentioning
confidence: 99%
“…ROS produced excessively would mediate detrimental effects, which are known as oxidative stress ( Rosenfeldt et al, 2013 ). It has been demonstrated that perioperative oxidative stress is associated with the increased risk of postoperative delirium ( Karlidag et al, 2006 ; Lopez et al, 2017 , 2020 ; Kazmierski et al, 2021 ). Similarly, in the present study, we found that anesthesia/surgery induced ROS accumulation and delirium-like behavior, while the ROS scavenger NAC attenuated these changes.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Kazmerski et al examining the relationship between oxidative stressors and the development of postoperative delirium, it was found that pre- and postoperative soluble receptors for advanced glycation end-product (sRAGE) levels were significantly higher in the delirium group compared to the non-delirium subjects. It was also found that preoperative sRAGE levels were significantly increased in patients with anxiety disorders [ 13 ]. Kazmerski et al further elicited a significant relationship between decreased oxidative stress capacity and the development of postoperative delirium; however, there were no significant findings of differences between pre- and post-operative antioxidant activity in patients with and without anxiety disorders [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that preoperative sRAGE levels were significantly increased in patients with anxiety disorders [ 13 ]. Kazmerski et al further elicited a significant relationship between decreased oxidative stress capacity and the development of postoperative delirium; however, there were no significant findings of differences between pre- and post-operative antioxidant activity in patients with and without anxiety disorders [ 13 ]. The limited data available suggests there may be a link between the development of postoperative delirium and patients who are suffering from anxiety due to increased advanced glycosylation end products.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between pre-and post-operative sRAGE and delirium was examined following cardiac surgery [134]. Delirium is accompanied by symptoms such as psychosis, confusion, and depression.…”
Section: Schizophreniamentioning
confidence: 99%